2019
DOI: 10.1021/acscatal.8b04272
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Acid Site for Selective Catalytic Oxidation of NH3 over Au/Nb2O5

Abstract: Selective catalytic oxidation (SCO) of NH3 to harmless N2 and H2O is an ideal technology for its removal. To develop air purification systems for a living environment, catalysts that can work at room temperature with high selectivities to N2 are required. However, it has been a technical challenge because the reported catalysts either needed high operating temperatures or showed low selectivities to N2. In this study, we first demonstrated that acidic metal-oxide-supported gold catalysts showed good N2 selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 36 publications
1
65
0
1
Order By: Relevance
“…Then N 2 gas was introduced at −180 °C with a flow rate of 50 mL min −1 for 30 min to fully exclude the gas phase and weakly adsorbed CO species. 36–38…”
Section: Methodsmentioning
confidence: 99%
“…Then N 2 gas was introduced at −180 °C with a flow rate of 50 mL min −1 for 30 min to fully exclude the gas phase and weakly adsorbed CO species. 36–38…”
Section: Methodsmentioning
confidence: 99%
“…As discussed in the previous section, the catalytic activity of supported AuNPs catalysts is extremely dependent on the size of AuNPs. The preparation of supported AuNPs catalysts is certainly considered as a strategic aspect strongly affecting the size of AuNPs [32][33][34]. Among the various methods for the preparation of Au catalysts, the impregnation approach finds particularly frequent applications.…”
Section: Effect Of Gold Preparation Methodsmentioning
confidence: 99%
“…Thus, Lippits et al [77] observed the enhanced NH 3 conversion (full NH 3 conversion at 338 • C with N 2 selectivity below 50%) over Au/Al 2 O 3 after its doping with CeO x (able to provide and store oxygen) and Li 2 O (responsible for decreasing the catalyst acidity and thus improved oxygen adsorption). Recently, Lin et al [12] reported the acidic metal-oxide-supported gold catalyst (Au/Nb 2 O 5 ) with improved N 2 selectivity compared to other metal-oxide-supported gold catalysts (e.g., Au/SiO 2 , Au/Al 2 O 3 , Au/Fe 2 O 3 , etc., Figure 6a). Specifically, Au/Nb 2 O 5 contains both Brønsted and Lewis acid sites that allowed NH 3 oxidation according to hydrazine mechanism (N 2 H 4 as the intermediate) and imide mechanism (HNO as the intermediate), respectively (Figure 6b).…”
Section: Au-and Ru-based Catalystsmentioning
confidence: 99%
“…Various kinds of catalysts were studied for NH 3 -SCO, including noble metals (e.g., Ru [11]), supported noble metals (e.g., Au/Nb 2 O 5 , Au/ZrO 2 [12]), (mixed) metal oxides, supported metal oxides, modified zeolites (e.g., Pt-CuMgAlO x [13], Ag-USY [13]), etc. These groups of catalysts investigated in NH 3 -SCO were summarized by Jabło ńska et al [7,14], Gao et al [15] and Lan et al [16].…”
Section: Introductionmentioning
confidence: 99%